Educação católica em Palmeira dos Índios-AL : o Centro Educacional Cristo Redentor (1944-2013) - Moreira, Ana Cristina Lima (2014)
This paper aims to redeem the history of the Centro Educacional Cristo Redentor, doing a brief approach of its historical process and its influence as a catholic school in the day by day of the society from 40 s to the present days. The Centro Educacional Cristo Redentor is a school located in Palmeira dos Indios city, countryside of Alagoas state, and is the result of a history of catholic education, introduced in Brazil by the Jesuits since the nineteenth century which was expanded by other religious institutions such as the Daughters of Divine Love, founded in Austria and is still present in 16 countries. The Daughters of Divine Love came in Brazil in 1920 and, in the 40 s, settled in Palmeira dos Indios city. This paper presents the historical, social, religious and educational context lived by the school over 70 years of existence, emphasizing its influence on the religious education of people from that city by the teaching of Cristian values. The research was conducted by reading the documents belonged to the Congregation collection from the Nossa Senhora das Neves Province headquartered in Natal city, Rio Grande do Norte state and the school object of this study. Theoretical literature reviews were done focusing some studies about religion science so as to contextualize the facts lived by the Centro Educacional Cristo Redentor community. Some interviews were done with people who witnessed the school trajectory, providing data for the intended goals. The critical analyses allows to comprehend the historical moments lived during the educational changes which in turns marked the history of the referring catholic school over 70 years of tradition. This research is supposed to contribute to the History of the catholic education through memory and orality.